A taxonomy of clinical response to mood stabilizers. (21st June 2020) - Scott, Jan; Etain, Bruno; Nierenberg, Andrew; Bellivier, Frank
Abstract: Introduction: Although clinical practice guidelines (CPG) identify first, second‐ and third‐line mood stabilizer (MS) treatments, they rarely define clinical response to prophylaxis or the core issues to be considered. This project aimed to develop a template for describing how clinical response may be classified and a framework to assist decision‐making and monitoring of response in day‐to‐day practice. Method: A scoping exercise was undertaken followed by narrative synthesis of (a) qualitative and quantitative definitions of MS response applied in clinical and research practice and (b) potential confounders (eg, non‐adherence; tolerability issues) of relevance to routine practice, for example, the concepts are applicable to individuals with bipolar disorder for whom sustained remission is a less realistic goal. Expert consensus was employed to develop a taxonomy of response and key concepts that inform clinical judgements about MS response. Results: Five core constructs can be used to systematize clinical judgements regarding MS response and its monitoring: (a) quantitative, qualitative and/or patient‐reported outcome measures (PROMS), (b) personalized assessment of the acceptable benefit‐to‐harm ratio of a proposed treatment, (c) adequacy of treatment exposure (dose, duration, therapeutic monitoring and adherence), (d) illness activity pre‐ and post‐MS initiation, and (e) other potential confounders (co‐prescription of MS; polypharmacy) or protective factors (eg, psychosocial factors). Conclusions: This heuristic framework might be used as a teaching aid or by clinicians who wish to take a more systematic approach to developing shared criteria for judging MS response that better match patient expectations and preferences. Heuristic approaches also allow seamless introduction of new evidence.